Pengaruh Auditor Responsibility, Professional Skepticism Dan Internal Control Terhadap Fraud Detection - Calvin Lazuardi, Hendro Lukman, Henny (Fakultas Ekonomi, Universitas Tarumanagara, 2019)
The objective of this research is to obtain empirical evidence about the effect of auditor responsibility, professional skepticism and internal control to fraud detection from the perspective of external auditor in Jakarta, Indonesia. This study used 65 external auditors as samples selected by convenience sampling. The data are primary data using questionnaires. The results of this research indicate that auditor responsibility does not have a significant effect on fraud detection, professional skepticism and internal control have a significant influence on fraud detection.